News Framing of Assets of Trading Victim Indra Kenz Seized by the State - Frisila Ayu Fitriyanti; Athok Murtadhlo (LPPM Stikosa-AWS, 2023)
This research aims to understand how the TVOneNews television media constructs news about the fate of the assets of the victim of illegal trading on Binomo, Indra Kenz, being seized by the state. Because Indra Kenz, the victim of illegal trading on Binomo, was judged as a gambler by the judge, and the assets were confiscated by the state. According to experts in the Anti-Money Laundering Act (TPPU), there were no gambling charges filed, only charges of money laundering against Indra Kenz. The purpose of this research is to examine how the